Influence of periodontal infection as a possible risk factor for preterm low birth weight - Rajesh K Thakur; Bipin K Yadav; Rafat Sultana; Shakeb K Afridi; Debasmita Das; Sheetal K Sahoo (Wolters Kluwer Medknow Publications, 2020)
Background: There is emerging interest and increasing amount of evidence that support the interrelationship between periodontitis and systemic conditions. Epidemiological and microbiological-immunological studies have lent credence to the concept that periodontal disease may be a separate risk factor for cardiovascular disease, cerebrovascular disease, and respiratory disease, as well as preterm delivery of low-birth-weight infants. Aim: The aim of this study was to evaluate the influence of periodontal infection as a possible risk factor for preterm low birth weight (LBW) based on age, literacy, and hemoglobin level of mother. Materials and Methods: The observational study was conducted on 200 subjects, which were selected from the free labor ward, District Hospital, Saifai, Etawah, UP, India. Periodontal examinations were performed using the World Health Organization criteria. The periodontal status of the mother was recorded using Community Periodontal Index. Results: For this study, chi-square test was performed to know the effect of variables and to find out the statistical significance of the study. Age of mother shows statistical insignificant association with periodontal disease, whereas literacy of mothers showed statistical significant association with periodontal disease, and periodontal status and hemoglobin levels of the mothers also showed a significant association. Conclusion: The prevalence of LBW infants was considerably less in mothers with a healthy periodontium and increased with progressive periodontal disease.